INTERVENSI EDUKASI GIZI BERBASIS KADER TERHADAP KEPATUHAN DIET LANSIA DENGAN HIPERTENSI DI WILAYAH PERDESAAN - Ulfa Hrp, Fitri Aidani; Hutagalung, Suzanne C (Universitas Pahlawan Tuanku Tambusai, 2025)
Hipertensi banyak dialami lansia, terutama di daerah perdesaan yang minim akses informasi dan tenaga kesehatan. Salah satu cara mengendalikan tekanan darah adalah melalui diet rendah garam dan bergizi seimbang. Penelitian ini bertujuan mengetahui apakah edukasi gizi yang dilakukan oleh kader kesehatan bisa meningkatkan kepatuhan diet lansia hipertensi. Penelitian dilakukan di dua desa terpencil dengan 80 lansia, dibagi menjadi dua kelompok: intervensi dan kontrol. Kelompok intervensi mendapat edukasi dari kader selama 8 minggu, sementara kelompok kontrol hanya mendapat penyuluhan satu kali dari tenaga kesehatan. Kepatuhan diet dan tekanan darah diukur sebelum dan sesudah intervensi. Hasilnya, kelompok intervensi lebih patuh pada diet dan mengalami penurunan tekanan darah yang lebih besar. Kader juga menunjukkan peningkatan kemampuan dalam memberi edukasi. Kesimpulannya, pendekatan ini efektif dan layak diterapkan di wilayah yang kekurangan tenaga kesehatan. Hypertension is a major non-communicable disease affecting older adults, especially in rural areas with limited access to health services and nutritional education. Compliance with a low-sodium and balanced diet is essential in managing blood pressure, yet remains low among the elderly in remote regions. This study aimed to assess the effectiveness of a cadre-based nutritional education intervention in improving dietary compliance among elderly patients with hypertension in rural settings. A quasi-experimental study with a pre-post control group design was conducted involving 80 elderly individuals with hypertension from two remote villages. Participants were selected using purposive sampling and divided equally into intervention and control groups. The intervention group received structured nutritional education from trained community health cadres over 8 weeks, while the control group received a single educational session by health professionals. Dietary compliance was measured using a modified Food Frequency Questionnaire (FFQ), and systolic blood pressure was recorded before and after the intervention. The intervention group showed a significant improvement in dietary compliance scores (p < 0.01) and a greater reduction in systolic blood pressure (mean decrease of 8.5 mmHg) compared to the control group (2.1 mmHg). Furthermore, cadre training improved communication skills and nutritional knowledge among local health volunteers. Cadre-based nutritional education is effective in enhancing dietary compliance and reducing blood pressure among hypertensive elderly individuals in rural areas. This community-based approach offers a practical and sustainable strategy for health promotion in underserved regions.